The Pin Note Cam: A Mobile Fault and Damage Reporting System - Halimaton Saadiah Ibrahim,; Mohamad Farhan Mohamad Mohsin, (Multidisciplinary Applied Research and Innovation, 2021)
With the development of the information era, people can access information anywhere and anytime using their smartphones with just a simple touch. However, people are sending information about infrastructure damage to media social sites instead of sending it to the correct organization. This is because making a report on infrastructure damage had been difficult for people as they need to follow some procedures and formalities in order to report the infrastructure damage to the relevant parties. Hence, a mobile application is proposed to solve the problem by providing faster alternative with photo capture capabilities and location recognition for the people to lodge and manage their reports on the infrastructure damage. This mobile app is called Pin Note Cam: A Mobile Fault and Damage Reporting System. The methodology used for this mobile application development is Rapid Application Development (RAD) where the requirements were gathered and the questionnaire used was Software Usability Measurement Inventory (SUMI). This questionnaire was carried out to evaluate the usability of the application. The evaluation was conducted on 31 respondents of students, staff, and JPP in UUM. The findings show that the respondents were satisfied with the ease of use and attractive interface design of Pin Note Cam. Hopefully, Pin Note Cam can provide a platform for the students, staff and JPP in UUM to create and manage their report on infrastructure damage. On the other hand, the functionality and the interactiveness of the interface can be improved in the future so that people can create and manage their reports easier.